Gilteritinib Enhances Anti-Tumor Efficacy of CDK4/6 Inhibitor, Abemaciclib in Lung Cancer Cells - Sun, Chao-Yue; Talukder, Milton; Cao, Di; Chen, Cun-Wu (Frontiers in Pharmacology, 2022)
Abemaciclib, a CDK4/6 inhibitor, is effective for the treatment lung cancer cells in preclinical studies, but its clinical results show that monotherapy with abemaciclib has no obvious superiority to treat lung cancer patients. Here we show that gilteritinib is an FDA-approved drug for treatment of acute myeloid leukaemia that enhances the cytotoxicity of abemaciclib via inducing apoptosis and senescence in lung cancer cells. Interestingly, abemaciclib in combination with gilteritinib induces excessive vacuoles in lung cancer cells. Mechanistically, abemaciclib in combination with gilteritinib results in AKT and Rb pathways inactivation in lung cancer cells. In addition, using RNA-sequencing, we found that combination of abemaciclib with gilteritinib induces G2 phase cycle-arrest, and inhibits DNA replication, homologous recombination in lung cancer cells. Of note, abemaciclib-resistant lung cancer cells are more sensitive to gilteritinib treatment. In mouse xenograft model, combination of abemaciclib with gilteritinib is more effective than either drug alone in suppressing tumor growth, with a safety profile. Together, our findings support the combination of abemaciclib with gilteritinib in the treatment of lung cancer, and suggest it should be evaluated in a clinical trial.